Relationship between diabetes diet-related quality of life and dietary fiber intake among people with type 2 diabetes: a cross-sectional study - Fuyuko Takahashi; Yoshitaka Hashimoto; Ayumi Kaji; Ryosuke Sakai; Yuka Kawate; Yuriko Kondo; Takuro Okamura; Naoko Nakanishi; Saori Majima; Takafumi Osaka; Hiroshi Okada; Takafumi Senmaru; et al. (Endocrine Journal)
Diet therapy is one of the most important treatments for people with type 2 diabetes (T2D). However, dietary restrictions due to diet therapy may reduce quality of life (QOL). This cross-sectional study aimed to investigate the association between diabetes diet-related QOL and dietary fiber intake in 238 people with T2D. The Diabetes Diet-related Quality of Life–Revised version (DDRQOL-9-R) and the brief-type self-administered diet history questionnaire were used to evaluate diabetes diet-related QOL and nutritional intake, respectively. Higher scores of each DDRQOL-9-R subscale means greater satisfaction with diet, perceived merits of diet therapy, and lower burden of diet therapy, which indicates good QOL. The median scores for perceived merits of diet therapy, satisfaction with diet, and burden of diet therapy were 58.3 [41.7–75.0], 75.0 [66.7–91.7], and 66.7 [50.0–75.0] points, respectively. HbA1c levels in people with high perceived merits of diet therapy (7.3 [6.7–7.8] vs. 7.5 [7.1–8.2] %, p = 0.007) and people with high satisfaction with diet (7.3 [6.8–7.8] vs. 7.5 [7.1–8.4] %, p = 0.010) were lower than those without. Dietary fiber intake was higher in people with high perceived merits of diet therapy (11.6 [8.8–16.7] vs. 10.0 [7.9–13.8] g/day, p = 0.010), high satisfaction with diet (11.4 [8.8–16.1] vs. 9.7 [7.8–13.2] g/day, p = 0.007), and low burden of diet therapy (11.8 [8.7–16.5] vs. 9.7 [7.8–12.6] g/day, p = 0.004) than in those without. Dietary fiber intake was related to perceived merits of diet therapy (Odds ratio [OR]1.07 [95%CI: 1.00–1.15], p = 0.049), burden of diet therapy (OR 0.90 [95%CI: 0.82–0.98], p = 0.022), and satisfaction with diet (OR 1.18 [95%CI: 1.09–1.27], p < 0.001) after adjusting for covariates. Dietary fiber intake is associated with diabetes diet-related QOL in people with T2D.